Urgensi Pengaturan Tentang Peralihan Hak Atas Merek Sebagai Objek Jaminan Fidusia - Amrulla, Mohammad Fahrial (Jurnal Cakrawala Hukum, 2018)
His study aims to find out that these researchers are meant to address the importance of the transfer of rights to a trademark that is used as a fiduciary jinminary object. So it can be seen that the importance of the arrangement of the transfer of rights to the trademark as the object of fiduciary collateral can provide legal certainty for the creditor and debtor as well as to know what legal factors causing the transfer of the trademark can not be applied if the trademark becomes the object of fiduciary collateral. type of normative research. From the research that has been done obtained the result that substantially Law no. 42 of 1999 on Fiduciary Guaranty and Law No.20 of 2016 on Trademarks and Geographical Indications have not been able to provide clarity in interpreting Article 1 number (1) of Law no. 42 of 1999 on Fiduciary Collateral, as well as Article 41 of Law No.20 of 2016 on Trademarks and Geographical Indications, and Section 499 of the Civil Code.How to cite item:Â Amrulla, M. (2018). Urgensi Pengaturan Tentang Peralihan Hak Atas Merek Sebagai Objek Jaminan Fidusia.Â Jurnal Cakrawala Hukum, 9(2), 135-141. doi:https://doi.org/10.26905/idjch.v9i2.2767